COMMON ERRORS OF ENGLISH FINAL CONSONANT CLUSTERS BY ADVANCED ENGLISH EDUCATION STUDENTS - Luthfy Al Razieb; Saadillah; Sovia Rahmaniah (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2021)
Student of English Education Department as a teacher candidate have to be good in producing English sounds, because they will be a teacher in the future which is students will imitate what they are saying. But, in reality mispronunciation is still frequently found in students of English Education Department, moreover to the advanced English education students. This research was using descriptive quantitative approach. And the objectives of this research were to know advanced English education students’ ability in pronouncing English final consonant clusters and what are the factors influences. The result showed that there were 44 pronunciation errors from 50 final consonant clusters that has been tested. Furthermore, many Advanced English Education students are unable to pronounce particular final consonant clusters. They tend to make error when they pronounce words containing /nd/, /mp/, /rst/, and /kst/ final consonant clusters. Based on the findings and discussion, it can be concluded that many of Advanced English Education students are still unable to pronounce English final consonant clusters correctly. They tend to get rid one sound at the end of the word because of interlingual factor, their friendship circle and their efforts in exploring the target language.